Population pharmacokinetic analysis of rivaroxaban in healthy volunteers and patients with radiofrequency ablation of non-valvular atrial fibrillation in China - Gu, Fangfang; Tang, Kaixian; Zhang, Cong; Hu, Mingsheng; Sun, Junlong; Yu, Xiang; Tian, Mengli; Zhang, Chen; Chen, Yingrong (Frontiers in Pharmacology, 2025)
AimsThis study aimed to develop a population pharmacokinetic (PopPK) model of rivaroxaban in healthy volunteers and patients with radiofrequency ablation of non-valvular atrial fibrillation (NVAF) in China and investigate the effect of potential covariates on pharmacokinetic (PK) parameters.MethodsPlasma concentrations of rivaroxaban with demographic data, biochemical indicators, and genetic data were derived from a bioequivalence study in 36 healthy volunteers and a real-world study containing 105 patients with NVAF. A PopPK model of rivaroxaban was performed with NONMEM software using a nonlinear mixed-effect modeling approach, and covariate impact on rivaroxaban pharmacokinetics was investigated.ResultsA two-compartment model characterized by first-order absorption and first-order linear elimination successfully described the pharmacokinetic properties of rivaroxaban. In the final PopPK model, the clearance rate for patients was 8.35 L/h, and the central and peripheral volumes of distribution were 19.7 L and 71.8 L, respectively. The creatinine clearance, ABCB1 rs1045642, and morbid state were identified as significant covariates affecting the clearance of rivaroxaban. The AUC0-inf increased by 58% for patients with moderate renal impairment compared to subjects with normal renal function. The AUC0-inf for patients with the wild genotype of ABCB1 rs1045642 was 25% higher than that for other genotypes. The validation results demonstrated the good predictability of the model, which was accurate and reliable.ConclusionThe PopPK model of rivaroxaban in healthy volunteers and patients with NVAF developed in this study was expected to help provide relevant PK parameters and covariate information for further studies of rivaroxaban. The study indicated that a daily dose of 15 mg may be appropriate as the primary dosage of rivaroxaban for Chinese patients with NVAF. A lower dose is recommended for patients with moderate renal impairment to avoid overexposure.